A survey on inhalation effect of essence of peppermint on nausea and vomiting after abdominal surgery in patients who have been admitted to Besaat and Tohid hospitals in Sanandaj - Najafi, bahareh; Ghahrisarabi, alireza; Esmaeili, roghayeh; Alavi Majd, hamid; Mojab, faraz (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Nausea and vomiting is among the most common complications in patients recovering from general anaesthesia , 30-70 of patients experience nausea and vomiting after surgery. Although variety of medications have been used to control this complication, it still remains as a problem. Armothpy a non pharmacologic intervention is suggested for treatment of many conditions and Pepprmint may be effectivein treatment of common digestive conditions. This aim of this study was to examine the efficacy of inhaling peppermint essence for prevention of nausea and vomiting after abdominal surgery in patients admitted in Beasssat and Tohid hospitals in Sanandaj in 2011. Method and materials: A randomized clinical trial was conducted to examine the efficacy of Peppermint essence inhalation for prevention of post- surgical nausea and vomiting. The sample of the study consisted of 90 patients, which were randomly allocated to receive peppermint inhalation or saline normal. A 2 × 2 gauze pad saturated with two drops of pure pharmacy-grade peppermint essence was used for 1 minute in intervention group. For patients in control group a 2 × 2 gauze pad saturated with 0. 9% normal saline was used. A visual analog scale was used to rate nausea. Patients were followed in recovery and surgical ward for occurrence of nausea and vomiting. Data were analyzed by SPSS software, version 17. Findings: There was not statistical difference between two groups in terms of confounding variables such as body mass index, length of anesthesia as well as type of anesthesia. 6. 7% of patients in peppermint group and 0% of patients in control group experienced mild nausea. Manwitney statistical test, showed no significant difference between the two groups in terms of nausea in recovery room. The results indicated there was significant difference between the two groups in the 1392 ناتسمز ،83 هرامش ،23 هرود / 34 ناراکمه و یفجن هراهب severity of nausea in surgical ward. There was not a significant difference between two groups in term of numbers of vomiting. Conclusion: The findings of the study showed no diferrence between peppermint and saline in terms of prevetion of nausea and vomiting. One reason can either be ineffective breathing patterns of patients after anesthesia or insufficient dose of peppermint which has affected the results of this study. It seems more studies with various shapes and amounts of peppermint are required in this regard. Keywords: Aromaterapy, Nausea & Vomiting, Peppermint REFERENCES Anderson L A , Gross B (2004); "Aromathrapy with peppermint isopropelalchol ,or placebo is equally effective in reliving post operative nausea". Journal of peri Anesthesia Nursing . 19(1) 35-29. Chadhary S et al (2008); "Preoperation intravenous fluid therapy with crystalloid or colloid on post operativenausea&vomitin". Indian Journal of Medical Research . 127(1) 577-581. Dieneman J et al(2012) "Risk factor of patient with and without post operative Nausea". PeriAnesthesia Nursing . 27(4) 258-252. Dubravaska L et al (2010); "Incidence of post operative nausea and vomiting in patients at a university hospital". Biomed Pap med Fac Unit PalackyOlomuc Czech Repub . 157(1) 69-79. Ferruggiari L et al (2012); "The effect of aromatherapy on post operative nausea in women undergoing surgical procedures". Journal of Perianesthesia Nursing . 27(4(246-251. Gan T G et al (2003); "Consenus guid lines for managing post operative nausea and vomiting". International Anesthesia Research Society . 97(16) 2-71. Gan T G et al (2007); "Societyfor ambulatory anesthesia guid lines for the management of post operative nausea and vomiting". Anesthesia & Analagesia . 105(1)16-25. Hunt R et al (2012); "Aromatrapy as treatment for post operative nausea. A randomized tril". International Anesthisia Analagesia Research Socity . 1(1)1-8. Pellegrin J et al (2009); "Comparison of inhalation of isopropyl alcholvsprometazin in the treatment of post operative nausea and vomiting(ponv) in patients identified as at high risk for developing ponv". AANA Journal . 77(4) 293-299. Salehisormaghi MH (2008); Herb and Herbal Therapy . Second ed. Tehran: Doniaetaghzie. Smeltzer S Bare B (2011); Textbook of Medical- Surgical Nursing, Operating Room . Translated by Khachian 1392 ناتسمز ،83 هرامش ،23 هرود / 32 ناراکمه و یفجن هراهب A. Tehran Jameae Negar. (Persian). Shaha PP , Kundnani PKM (2004); "A review of medicinal uses and pharmacological effects of menthe pipprita". Natural Product Radiance . 3(4) 214-224. Tate S (1997); "Peper mint oilatreatment for postoperative nausea". Journal of Advanced Nursing . 26(1) 584-590.